2022
DOI: 10.18502/acta.v60i1.8325
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio Cut-Off Point for COVID-19 Mortality: A Retrospective Study

Abstract: Several months have passed since the onset of the COVID-19 pandemic. Multiple characteristics have been proposed as prognostic factors so far. This study aims to provide evidence on the association of neutrophil-to-lymphocyte ratio (NLR) at the hospitalization time and three desired outcomes (mortality, prolonged hospitalization, and intensive care unit [ICU] admission). We designed a single-centre retrospective observational study in Baharloo Hospital (Tehran, Iran) from 20 February to 19 April 2020. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
2
5
1
Order By: Relevance
“…This result is in line with studies that higher NLR at admission is associated with an increased risk of death [34,35]. The study by Kheyri et al, 2022, showed that the first results of NLR upon admission to the hospital were independently significant (p < 0.0011) with death and care in the intensive care unit [35]. A retrospective cohort also showed significant results (p = 0.0147), where each unit increase in NLR was associated with an 8% increase in the risk of death [26].…”
Section: Effect Of Nlr On Covid-19 Outcomesupporting
confidence: 92%
See 4 more Smart Citations
“…This result is in line with studies that higher NLR at admission is associated with an increased risk of death [34,35]. The study by Kheyri et al, 2022, showed that the first results of NLR upon admission to the hospital were independently significant (p < 0.0011) with death and care in the intensive care unit [35]. A retrospective cohort also showed significant results (p = 0.0147), where each unit increase in NLR was associated with an 8% increase in the risk of death [26].…”
Section: Effect Of Nlr On Covid-19 Outcomesupporting
confidence: 92%
“…The results of this study show a significant effect of NLR on the outcome of COVID-19. This result is in line with studies that higher NLR at admission is associated with an increased risk of death [34,35]. The study by Kheyri et al, 2022, showed that the first results of NLR upon admission to the hospital were independently significant (p < 0.0011) with death and care in the intensive care unit [35].…”
Section: Effect Of Nlr On Covid-19 Outcomesupporting
confidence: 87%
See 3 more Smart Citations